Vehicle Speed Estimation System by using Matlab - Che Manan, Che Mohd Safwan Najmi; Wan Mahmud, Wan Mahani Hafizah (Evolution in Electrical and Electronic Engineering, 2021)
One of the biggest issues inside the UTHM community was the vehicle over speeding issue. As a result of this problem, all car drivers within inside the UTHM area exceed the speed limit. Besides that, The Vehicle Speed Estimation System by MATLAB simulation software’s was created to address this issue. This system was built with the ESP32 Camera Module, and the video pictures were processed with the MATLAB software. Any vehicle exceeding the speed restriction within the UTHM area will be recorded and captured by this camera recorder system. The MATLAB will display the offender vehicle’s exact speed as proof that it is exceeding the speed restriction in that location. This project will aid in the reduction of excessive speeding inside the Universiti Tun Hussein Onn Malaysia area. This project is also being created with the goal of lowering the accident rate in the UTHM area and generating a more controlled and effective speed movement. As a result, the entire UTHM community will take this matter more seriously and drive within the speed limit within the UTHM area, as well as build a new better driving environment within the UTHM area by paying closer attention to the car speedometer.